Corporate financing and target behavior: New tests and evidence - Chauhan, Gaurav Singh; Huseynov, Fariz (Journal of Corporate Finance, 2018)
This study addresses the recent concerns in the capital structure literature about the reliability of tests of the target-following behavior. Using a novel testing strategy, we examine whether and to what extent firms' financing choices–rather than the movement of their debt ratios per se – concur with the target-following behavior. We find that firms' financing decisions are not generally consistent with systematic target-following. Our results remain similar when we examine an extended period of time and also when we consider that firms may have a range of target debt ratios rather than a unique target or varying financial constraints. Our results are also robust to different target specifications and our methodology can reliably distinguish the target behavior from random financing. Further tests also confirm our results by suggesting that the firms' financing decisions are not primarily driven by deviations from the firms' target debt ratios.